Report on the Observance of Standards and Codes, Accounting and Auditing : Module B - Institutional Framework for Corporate Financial Reporting, B.6 Accountancy Education - World Bank (Washington, DC: World Bank, 2017)
The purpose of this report is to gain an understanding of the institutional environment underpinning accountancy education at the tertiary level as well as the practices followed by leading universities in the teaching of accountancy. Questions are based on examples of international good practice for the education of aspiring accounting professionals and auditors such as the International Education Standards (IESs) issued by the International Accounting Education Standards Board (IAESB). The report is structured as follows: institutional environment for accountancy education; admission criteria; accountancy curriculum; and post-university career.